2002
DOI: 10.1073/pnas.212515999
|View full text |Cite
|
Sign up to set email alerts
|

B cells develop in the zebrafish pancreas

Abstract: The zebrafish, with its transparent free-living embryo, is a useful organism for investigating early stages in lymphopoiesis. Previously, we showed that T cells differentiate in the thymus by day 4, but no sites for B cell differentiation were seen until 3 weeks. We report here that on day 4, we detect rearrangements of genes encoding B cell receptors in DNA extracted from whole fish. Also by day 4, rag1 transcripts are seen in the pancreas, an organ not previously associated with lymphopoiesis; by day 10, Ig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 36 publications
8
77
0
2
Order By: Relevance
“…The first location is consistent with data in mammals where cryptopatches in the lamina propria are associated with the generation of IEL (Matsunaga 1998;Cheroutre 2004). In contrast to our data, rag-1 was abundantly expressed in both intestinal epithelium and lamina propria in zebrafish (cyprinidae) (Danilova and Steiner 2002), suggesting that the extent of extrathymic T cell production might differ among fish species.…”
Section: Discussionsupporting
confidence: 92%
“…The first location is consistent with data in mammals where cryptopatches in the lamina propria are associated with the generation of IEL (Matsunaga 1998;Cheroutre 2004). In contrast to our data, rag-1 was abundantly expressed in both intestinal epithelium and lamina propria in zebrafish (cyprinidae) (Danilova and Steiner 2002), suggesting that the extent of extrathymic T cell production might differ among fish species.…”
Section: Discussionsupporting
confidence: 92%
“…TCRα chain expression begins in the zebrafish thymus at 4 dpf (Danilova et al, 2004) two days after the appearance of the first lymphoid cells in the organ (Willett et al, 1999). Studies also demonstrated the pronephros as the first extrathymic site of Rag-2 expression at 8 dpf (Trede et al, 2004), and Rag1 was observed expression in the zebrafish pancreas by day 4 (Danilova and Steiner, 2002). These genes could be instrumental for studying the development and function of thymus in fish larval stages.…”
Section: Introductionmentioning
confidence: 94%
“…These secretory cells are analogues of the mammalian plasma cells and are known as antibody secreting cells (ASCs) or plasmablasts [31]. The largest concentration of B-lymphocytes exists in the pronephros and, accordingly, this region is also rich in immunoglobulins [32]. The incorporation of surface-bound immunoglobulins on the membrane of the B-cell is also naturally occurring and allows for further antigen interactions and subsequent pathogen removal or control.…”
Section: Teleost Adaptive Immunitymentioning
confidence: 99%